Left atrial remodeling after Mitraclip implantation. (25th November 2020) - Neri, G; Aquila, I; Albanese, M; Panuccio, G; Polimeni, A; Sabatino, J; Mascaro, G; Spaccarotella, C; Mongiardo, A; Indolfi, C
Abstract: Objective: Changes in left atrial (LA) size and function are associated with major adverse cardiovascular outcomes such as atrial fibrillation, heart failure, stroke, and death. Reverse LA remodelling occurs after successful surgical mitral valve repair for severe MR. Changes in LA volumes after MV repair have reported in several studies. However, LA data are limited in the setting of transcatheter repair. Materials an methods: From November 2016 to July 2018, clinical and echocardiographic data of 42 patients with mitral regurgitation who underwent Mitraclip implantation in our division were evaluated for LA function: LA global longitudinal strain (LA GLS); LAESV (Left atrial end-systolic volume), LAEDV (Left atrial end-diastolic volume); LA emptying Fraction at baseline, at 1 month, at 6 months and 1 year of follow up were assessed. The variation of continuous variables was evaluated using a student T test for paired data or the Wilcoxon matched-pair signed rank test when appropriate. The categorical variables between two groups were evaluated using the chi-square test (χ 2 ). P values <0.05 were considered significant. Results: The etiology of the mitral regurgitation was primary in 33, 3% and secondary in 66, 7% of the included patients. The MR degree was 3+ in 21, 4% of patients and 4+ in 78, 6%. When compared to baseline at 6 months and 1 year a statistically significant reduction was observed for both LAESV (p<0.001) and LAEDV (p<0.001). At 6 months, compared to baseline, the LA GLS reached statistic relevance (p 0.05) with a significant improvement at 1 year (p 0.001). Finally, we did not find significant differences in LA emptying fraction at different time point analyzed. Conclusions: A successful MitraClip procedure can reverse the process of LA remodeling within 12 months, and this can be detected by Two-dimensional speckle tracking echocardiography (2D STE) through an improvement in the LA reservoir function. These data generate the hypothesis that the GLS, compared to conventional echocardiographic parameters, represents an advanced method that quantify atrial function in Mitraclip implanted patients. Funding Acknowledgement: Type of funding source: Public hospital(s)